Essential oils – a review of the natural evolution of applications and some future perspectives - Stanislava Ivanova; Yana Gvozdeva; Radiana Staynova; Daniela Grekova-Kafalova; Vanya Nalbantova; Niko Benbassat; Nina Koleva; Kalin Ivanov (Pharmacia)
Since ancient times, essential oils (EOs) have been used, thoroughly explored, and regarded as products of great importance for humanity. Currently, EOs represent not only an important part of the contemporary pharmaceutical and cosmetic industry but are also considered as sources for novel drug candidates. The article discusses the applications of EOs in historical terms, the current applications, and the future perspectives. Although there are many studies that involve EOs, the therapeutic potential of EOs is not fully investigated. In the next decades it is highly likely that some compounds, isolated from EOs, could be included in the composition of novel drug candidates with targets in neurology, cardiology, or oncology. Moreover, EOs represent important key points in the development of novel environmentally friendly preservatives and pesticides.